2010
DOI: 10.1007/s00280-010-1434-6
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent anticancer effects of leptomycin B on lung adenocarcinoma

Abstract: Our results suggest that LMB has anti-cancer potential and provides a new regimen of individualized therapy for lung cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…46 LMB is the most extensively studied XPO1 inhibitor, and is a widely used biologic tool to define XPO1-mediated protein export. LMB was shown to be active preclinically in several solid tumor and hematologic tumor models 18,19,21,42 but was associated with a low therapeutic index in mouse studies because of off-target gastrointestinal effects, as well as profound doselimiting anorexia, fatigue, and gastrointestinal effects when introduced in a phase 1 study when given intravenously. 20 In this trial neither target validation of XPO1 inhibition nor etiology of nausea/emesis and fatigue were adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 LMB is the most extensively studied XPO1 inhibitor, and is a widely used biologic tool to define XPO1-mediated protein export. LMB was shown to be active preclinically in several solid tumor and hematologic tumor models 18,19,21,42 but was associated with a low therapeutic index in mouse studies because of off-target gastrointestinal effects, as well as profound doselimiting anorexia, fatigue, and gastrointestinal effects when introduced in a phase 1 study when given intravenously. 20 In this trial neither target validation of XPO1 inhibition nor etiology of nausea/emesis and fatigue were adequately addressed.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 To date, efforts to clinically pharmacologically inhibit XPO1 have been unsuccessful because of off-target effects. [18][19][20][21] A selective XPO1 antagonist may allow targeting of the TSPs axes in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Leptomycin B modifies CRM1 by a Michael-type covalent addition reaction at the reactive site (i.e., cysteine 528). In vitro studies have shown that leptomycin B induces acute cytotoxicity at concentration less than 5 μM for 1 h (Mutka, et al, 2009), and the agent was also active in preclinical solid and hematologic tumor models (Mutka, et al, 2009; Shao et al, 2011; Turner, et al, 2009). One of the potential clinical problems associated with leptomycin B that were discovered in preclinical tumor models was its low therapeutic index.…”
Section: Inhibitors Of the Crm1 Proteinmentioning
confidence: 99%
“…8, 9 In addition, multiple studies show that inhibition of CRM1 induces apoptosis and inhibits tumor growth in several cancer cell lines. 10, 11 However, despite abundant knowledge of subcellular TSP localization being important in RCC behavior, 12 there are no published studies of CRM1 inhibition in RCC.…”
Section: Introductionmentioning
confidence: 99%